(untitled) (Bioresearch Communications, 2024)
A study of avifauna in Kaliganj upazila in Jhenaidah district was conducted from July 2020 to June 2021, using direct field observation method. A total of 153 species and 6175 individuals were observed, with the highest diversity of birds (64 species, 41.83%) recorded in the order Passeriformes and 10 species under family Accipitridae. The site with the highest species richness (136 species) and abundance (2308 individuals) was Maliat, characterized by low anthropogenic disturbance, whereas the lowest was at Kaliganj municipality, with high anthropogenic disturbance. Bird communities across the three-study sites showed significant differences in non-metric multidimensional (NMDs) plot analysis. Species richness and abundance varied significantly across the three seasons, with the highest avian species diversity recorded in winter and the most even distribution in the rainy season. Homestead forest was the most frequently used microhabitat, with birds predominantly observed in trees. The most abundant bird species was Spilopelia chinensis (264 individuals, 4.27%). Observation status of birds showed that 51 (33.33%) bird species were very common, 22(14.37%) common, 27(17.64%) uncommon, and 53(34.64%) were few. Fifteen species faced anthropogenic threats, particulalrly illegal hunting and the use of bird nests in agriculture, which was higher in winter, especially in the Barobazar area. This study on avian diversity and community provides valuable insights for the conservation of avifauna outside protected areas, particularly in human-dominated landscapes of sub-tropical countries like Bangladesh. Bioresearch Commu. 11(1): 1688-1697, 2025 (January)